Better health and ambient assisted living (AAL) from a global, regional and local economic perspective. (21st December 2010) - Eberhardt, Birgid; Fachinger, Uwe; Henke, Klaus-Dirk
A high degree of social and economic relevance has been attributed to the technologies of assistance, and to information and communication systems, by scientists and politicians alike, particularly in connection with the development, promotion, and organisation of so-called senior-friendly environments and with ambient assisted living (AAL). Assisting technologies aim to provide more support to meet daily needs and preserve autonomy and quality of life. The focus of this paper is on the aged of the future, their specific demands and resources, which these technologies should be able to serve while adhering to their individual requirements. These technologies can make a considerable difference to the way people are able to live together and may represent new opportunities to the providers of outpatient and inpatient nursing and medical care.